A scuola di singolarità: tra standard d’eccellenza e self-made-talent | Learning Singularity: Between Standards of Excellence and Self-Made Talent - Lai, Aurora Maria (SocietàMutamentoPolitica, 2025)
While the processes of singularization spread out the school, teaching takes on different postures. These, dictated by different orientations to value (old and new school), are characterized by practices and objectives diametrically opposed each other, articulated between the resistance of general and the innovation of particular. How is it possible despite this polarization that the outcome – in terms of which student’s behaviours are positively recognized – is unambiguously singularization? The biographical agency represents the activation of identity, caused by the compulsion to reflect (Rosa 2017) and the existential need to “be someone” (Martuccelli 2017b), and becomes progressively the objective of formal socialization. Although the criteria for evaluating life (and identity) project respond to the orientation of the teacher’s value – which are diversified – the rhetoric of sacrifice and merit permeates both declensions of recognition. On the one hand, old school tries to consecrate the standard of excellence; on the other hand, new school contributes to the construction of a unique biographical mechanism, the self-made-talent. Both are results of more or less explicit processes of inclusion/exclusion. Formal socialization – historically structured around the logic of the general – meets and clashes with the logic of the particular, affecting significantly the biographical and identity composition of the pupils.